Construction SMEs safety challenges in water sector in Oman. (April 2021) - Al Mawli, Bader; Al Alawi, Mubarak; Elazouni, Ashraf; Al-Mamun, Abdullah
Highlights: Safety challenges in construction SMEs in the water sector in Oman were investigated. A questionnaire from PEROSH was adopted in the study. The questionnaire was originally designed to meet the Zero Accident Vision study. Management safety justice and resilience had the lowest scores. Learning from incidents and safety-health preventive interaction are also challenges. Low safety empowerment affects safety climate in the construction SMEs. Abstract: The level of compliance of construction SMEs to the Occupational Health and Safety (OHS) in Oman is not satisfactory due to many issues including budget constraints, and big diversity of the culture of the construction workers. Resolving these issues can contribute potentially to upgrade the safety practices in the country. To pave the way of the upgrading, this study explores the prevailing understanding of the construction safety staff in Oman regarding factors including: (1) individual commitment to OHS, (2) management commitment to OHS, (3) effectiveness of communication, (4) safety priority, (5) safety justice, (6) safety empowerment, (7) learning from incidents, (8) safety climate, (9) Health, Safety, and Environment (HSE) learning conditions, (10) safety resilience/recovery after incidents, and (11) HSE preventive interaction. The current study was conducted using an online survey to identify the challenges that face the construction SMEs working in the water sector in Oman. The survey used in the current study was adopted from the survey of the Partnership for European Research in Occupational Safety and Health (PEROSH). The PEROSH survey which covers eleven dimensions encompassing 73 attributes was translated into four languages (English, Arabic, Urdu, and Hindi). A total of 335 surveys were distributed and eighty-eight responses were received and analyzed. The results of all dimensions, excluding the dimension of individual commitment to OHS, ranged between 2.43 and 2.96 out of 5 (Likert scale), which give clear indication of a pressing need for improvement. Accordingly, recommendations for improvements toward effective implementations of the ten OHS dimensions were introduced and reported in this study.